Biofilm Formation by Drug Resistant Enterococci Isolates Obtained from Chronic Periodontitis Patients - Bhardwaj, Sonia Bhonchal (J Clin Diagn Res, 2017)
INTRODUCTION: Enterococci are an important cause of opportunistic nosocomial infections and several multidrug resistant strains have emerged. The severity of periodontal diseases is managed by reduction in the pathogenic bacteria. There is a need to assess the prevalence and antibiotic susceptibility of enterococci colonizing the periodontal pocket and correlate its biofilm formation ability because oral biofilms provide a protective environment and are a reservoir of bacterial colonization of the gingival crevice. AIM: To investigate possible association between antibiotic susceptibility and biofilm formation in enterococci isolates from chronic periodontitis patients. MATERIALS AND METHODS: This retrospective study was conducted at Dr. Harvansh Singh Judge Institute of Dental Sciences and Hospital, Punjab University, Chandigarh from January 2015 to October 2015. Sterile paper points were inserted in the periodontal pocket of 100 subjects and put in a transport media. Forty -six isolates were identified as enterococci. The isolates were further examined for their ability to form biofilm by microtitre plate assay and antimicrobial susceptibility testing was done by disc diffusion method for clinically relevant antibiotics. RESULTS: Significant relationship (p<0.001) was found between biofilm production with antibiotic resistance to Vancomycin, Erythromycin, Ciprofloxacin, Tiecoplanin, Amoxycillin and Gentamycin. CONCLUSION: The study demonstrates a high propensity among the isolates of Enterococci to form biofilm and a significant association of biofilm with multiple drug resistance.